A light microscopic and ultrastructural examination of calcified dental tissues of horses: 1. The occlusal surface and enamel thickness - Kilic, S.; Dixon, P.M.; Kempson, S.A. (British Equine Veterinary Association, 1997)
Gross and microscopic examinations were undertaken on 46 cheek (molar and premolar) and 4 incisor equine teeth that were fractured, or sectioned either with a lathe or diamond saw. Specimens were examined without treatment, after decalcification or acid etching, utilising light, and scanning and transmission electron microscopy. In some horses, the occlusal surface of the teeth were covered with an organic pellicle. The occlusal surface of the underlying equine enamel contained different wear patterns, including polished areas, local fractures, wedge-shaped pits, striations and depressions. Occlusal dentine showed depressions whose depth was related to its occlusal surface area, with larger surface areas having deeper depressions. The thickness of equine enamel varied greatly throughout its folds in the transverse plane, and was thickest in areas where folds were parallel to the long axis of the maxilla and mandible. Enamel thickness remained constant in the longitudinal plane (throughout the length of the tooth). Peripheral enamel was more deeply infolded in lower than in upper cheek teeth and this appeared to compensate for the absence of infundibula (deep, cup-like enamel indentations that are partially filled with cement) in the lower cheek teeth.
Keywords: Calcified dental tissue; Enamel; Horse; Light and ultra-microscopy; Occlusal surface